CARBON SOURCE ON in vitro MULTIPLICATION OF ‘MC’ AND ‘ADAMS’ QUINCE ROOTSTOCKS - RIBEIRO, MIRIAN DE FARIAS; RITTERBUSCH, CRISTINA WEISER; BIANCHI, VALMOR JOÃO; PETERS, JOSÉ ANTONIO (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2015)
The objective was to determine the best carbon source and concentration for in vitro multiplication of quince MC and Adams cultivars. Nodal segments (1.0 cm and 1-2 buds) were inoculated in MS and as a carbon source, sucrose, fructose or sorbitol were used with the following concentrations: 0, 15, 30, 45 and 60 g L-1. After 60 days, it was observed that, for ‘MC’, 60 g L-1 sucrose and 30 g L -1 fructose yielded 100% sprouted explants. The highest shoot length average (1.49 cm) was obtained with 30 g L-1 sucrose and 60 g L-1 sorbitol. The concentration of 45 g L-1 provided the highest number of shoots (1.76), higher fresh mass (0.058 g) and higher dry matter (0.02 g), regardless of the carbon source. For ‘Adams’, the highest number of shoots (1.47) was obtained with sucrose and the higher dry mass of shoots (0.01 g) was obtained with sucrose and sorbitol. The sucrose concentration of 30 g L-1 provided the highest shoot lenght average (2.14 cm) and higher fresh weight (0.1 g) and 45 g L-1 sorbitol provided greater dry mass of shoots (0.03 g ). The highest percentage of sprouted explants was obtained at a concentration of 30 g L-1 (79.58%) and sucrose as carbon source (71.25%). The highest average number of shoots (1.45) was obtained with 30 g L-1. It was concluded that 45 g L-1 sucrose for ‘MC’ and 30 g L-1 sucrose for ‘Adams’ were the best concentrations for in vitro multiplication.